Thinking, Feeling, Reading: On Methodologies in Scholarship on Malaysian Literature in English - Lim, David (SARE: Southeast Asian Review of English, 2021)
This essay is about the production of scholarship on Malaysian literature in English, specifically exegeses derived from the application of the art of reading known as hermeneutics. Its argument is that the overwhelming majority of existing readings of said literature is based on the methodology of critique, and that over-reliance on critique puts at risk the vitality of the scholarship in question. The essay then proposes postcritical methodologies that are centred on the affects as alternative ways of reading, before putting them to work on Lee Kok Liang’s Flowers in the Sky, a classic Malaysian text, demonstrating their potential contribution to diversifying conversations about Malaysian literature in English.